International File: The Finer Points of Working in England’s ORs - Wright, Lucy (Operating Room Nurses Association of Canada Journal, 1993)
The fundamental philosophy behind quality patient care is international; the specialised area of OR nursing should be less susceptible to international differences. Yet, the experience of moving to a different country reveals the extent of the actual cultural and professional variations available. The subtle, yet real, practical differences observed by a Canadian OR nurse, after working in England for two years, are examined.